Eksistensi Perempuan Tokoh Utama dalam Antologi Cerpen Kabut di Teras Senja Karya Sutini: Kajian Feminisme - Nadia Ulil Azmi; Sugiarti Sugiarti; Herni Fitriani (Universitas Palangka Raya, 2024)
This research aims to describe the forms and strategies used by the main female character in fighting for her existence. The method used in this research is a qualitative descriptive method. The results of the research found that the forms of existence of the female main character in the short story anthology Kabut di Teras Senja by Sutini are events experienced by the main character in her relationship with other people and her environment which shows and strengthens her existence as a woman. In the short story anthology Kabut di Teras Senja by Sutini there are sentences and paragraphs that show the experiences of the main character in the short story anthology Kabut di Teras Senja by Sutini such as women can work, women can become intellectuals, women can work to achieve social change in society and women can reject his otherness. The strategy used by the main character in fighting for his existence in the short story anthology Kabut di Teras Senja by Sutini contains 6 short story titles and 26 existence strategies were found, including: women can work (8), women can become intellectuals (9), women can work for achieve social change in society (5) and women can reject their otherness (4).